Beta‐thymosin gene polymorphism associated with freshwater invasiveness of alewife (Alosa pseudoharengus). Issue 4 (30th January 2014) - Michalak, Katarzyna; Czesny, Sergiusz; Epifanio, John; Snyder, Randal J.; Schultz, Eric T.; Velotta, Jonathan P.; McCormick, Stephen D.; Brown, Bonnie L.; Santopietro, Graciela; Michalak, Pawel
ABSTRACT Predicting the success of a species' colonization into a novel environment is routinely considered to be predicated on niche‐space similarity and vacancy, as well as propagule pressure. The role genomic variation plays in colonization success (and the interaction with environment) may be suggested, but has not rigorously been documented. To test an hypothesis that previously observed ecotype‐specific polymorphisms between anadromous and landlocked alewife (Alosa pseudoharengus) populations are an adaptive response to osmoregulatory challenges rather than a result of allele sampling at founding, we examined multiple anadromous and landlocked (colonized) populations for their allelic profiles at a conserved region (3′‐UTR end) of a β‐thymosin gene whose protein product plays a central role in the organization of cytoskeleton. The putatively ancestral β‐thymosin allele was prevalent in anadromous populations, whereas a newly derived allele was overrepresented in landlocked populations; a third allele was exclusive to the anadromous populations. We also conducted a complementary set of salinity exposure experiments to test osmoregulatory performance of the alewife ecotypes in contrasting saline environments. The pattern of variation and results from these challenges indicate a strong association of β‐thymosin with colonization success and a transition from species with an anadromous life history to one with only a freshwater component. J. Exp. Zool. 321A: 233–240, 2014. © 2014 Wiley Periodicals, Inc.